2014
DOI: 10.1016/j.jhazmat.2014.05.065
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of contaminant subslab concentration in petroleum vapor intrusion

Abstract: In this study, the development and partial validation are presented for an analytical approximation method for prediction of subslab contaminant concentrations in PVI. The method involves combining an analytic approximation to soil vapor transport with a piecewise first-order biodegradation model (together called the analytic approximation method, including biodegradation, AAMB), the result of which calculation provides an estimate of contaminant subslab concentrations, independent of building operation condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…Based on the evidences provided by the above-mentioned empirical studies, U.S.EPA (2015a) suggested that additional investigation may be not necessary when the source to building vertical separation distance is greater than 1.8 m (6 ft) for dissolved contamination or 4.6 m (15 ft) for light non-aqueous phase liquid (LNAPL). Furthermore, results from numerical (Hers et al, 2000;Abreu and Johnson, 2006;Abreu et al, 2009;Knight and Davis, 2013;Hers et al, 2014) and analytical models (DeVaull, 2007;Yao et al, 2014;Verginelli and Baciocchi, 2014;Yao et al, 2016) were consistent with the empirical exclusion distance values reported above, showing that, in nearly all cases, a source to building vertical separation distance greater than 2 m or 5 m is sufficient to attenuate to acceptable risk-based levels petroleum hydrocarbon vapors from dissolved-phase or LNAPL sources, respectively.…”
Section: Introductionsupporting
confidence: 78%
“…Based on the evidences provided by the above-mentioned empirical studies, U.S.EPA (2015a) suggested that additional investigation may be not necessary when the source to building vertical separation distance is greater than 1.8 m (6 ft) for dissolved contamination or 4.6 m (15 ft) for light non-aqueous phase liquid (LNAPL). Furthermore, results from numerical (Hers et al, 2000;Abreu and Johnson, 2006;Abreu et al, 2009;Knight and Davis, 2013;Hers et al, 2014) and analytical models (DeVaull, 2007;Yao et al, 2014;Verginelli and Baciocchi, 2014;Yao et al, 2016) were consistent with the empirical exclusion distance values reported above, showing that, in nearly all cases, a source to building vertical separation distance greater than 2 m or 5 m is sufficient to attenuate to acceptable risk-based levels petroleum hydrocarbon vapors from dissolved-phase or LNAPL sources, respectively.…”
Section: Introductionsupporting
confidence: 78%
“…According to the development of the model, the increase of the moisture content can decrease the effective diffusivities of soil gas and the upward advection, but increasing the biodegradation rate. In sum, a higher moisture content would lead to lower source-to-indoor air concentration attenuation factors with current conditions, similar to models based on diffusion dominated transport (2022, 42). Finally, it should be noted the influence of indoor air exchange rate is not significant here, differently from the sensitivity analysis results of the Johnson-Ettinger model in Johnston et al (4041), where different variations of indoor air exchange rate were employed.…”
Section: Resultssupporting
confidence: 54%
“…As employed in previous models (9, 2022, 24), a piecewise aerobic biodegradation is assumed here, shown as equation (T3) in Table 1, which means that a first-order reaction occurs if the oxygen concentration is larger than 1% v/v, otherwise, there is no reaction. The boundary conditions for contaminants and oxygen are shown in equation (T4) in Table 1.…”
Section: Model Developmentmentioning
confidence: 99%
“…In recent decades, there have been proposed numerous one‐dimensional (1D) analytical models (e.g. DeVaull ; Davis et al ; Verginelli and Baciocchi ; Yao et al ) and multidimensional numerical models (e.g. Abreu and Johnson ; Abreu et al ; Hers et al ) for estimating the migration of subsurface petroleum vapors into potentially impacted buildings.…”
Section: Introductionmentioning
confidence: 99%